The spread of financial sophistication through emerging markets worldwide - Kensinger, John W. (Bingley, U.K. : Emerald, 2016)
The broad theme of Volume 32 of Research in Finance is "The Spread of Financial Sophistication Through Emerging Markets Worldwide." Contributions assess the spread of Initial Public Offerings, the use of derivatives to provide stability, corporate governance in emerging markets, and the privatization of the Russian economy. We also gain new insights into applying financial modeling in emerging markets.
Total factor productivity, growth and entrepreneurship in emerging economies / Rita Biswas -- Estimating time-varying beta coefficients: an empirical study of US & ASEAN portfolios / Jordan French -- Comparative analysis of asset pricing models based on log-normal distribution and Tsallis distribution using recurrence plot in an emerging market / Kousik Guhathakurta, Basabi Bhattacharya, A. Roy Chowdhury -- Does liquidity risk premium affect optimal portfolio holdings of U.S Treasury securities? / Karoll Go<U+0301>mez Portilla -- Size, value, and momentum risk in the cross-section of average returns and volatility / Knut Lindaas, Prodosh Simlai -- IPO advertising: a possible cause of short-term overvaluation / Konpanas Dumrongwong -- A comparative study of the influence of derivatives on bank stability in emerging and recently developed countries: evidence from the last financial crisis / Mohamed Rochdi Keffala -- Is there a relationship between the liquidity of closed-end funds portfolios, fund ownership by smaller investors, and the liquidity of the funds shares? / Charles Cullinan, Xiaochuan Zheng, Elena Precourt -- Does demographic change impact Hong Kong economic growth? / Ping-fu (Brian) Lai, Wai Lun (Patrick) Cheung -- Does optimizing the cash conversion cycle ameliorate firm's performance? Unraveling the relationship in the Indian corporate landscape / Nityanand Tripathi, Naseem Ahamed -- Budget investments in Russia: not investment but transformation of public property / Dmitry Komyagin -- Speculative bubble on the Moroccan real estate market: identification and cycles / Firano Zakaria -- Corporate Governance Index in emerging markets: Peruvian listed companies / Edmundo Lizarzaburu, Luis Berggrun, Kurt Burneo -- Optimal arbitrage path in the foreign exchange market / Reza Habibi -- The misalignment phenomena in the foreign exchange market: evidence for the Tunisian Dinar / Salima ben Ezzeddine, Kamel Naoui.
Includes bibliographical references.
Print version record
Keywords: Business & Economics -- Finance; Finance; Finance; Finance -- Mathematical models